2015
DOI: 10.1016/j.neuroscience.2015.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperalgesic effect of tetrodotoxin in rat models of persistent muscle pain

Abstract: Persistent muscle pain is a common and disabling symptom for which available treatments have limited efficacy. Since tetrodotoxin (TTX) displays a marked antinociceptive effect in models of persistent cutaneous pain, we tested its local antinociceptive effect in rat models of muscle pain induced by inflammation, ergonomic injury and chemotherapy-induced neuropathy. While local injection of TTX (0.03-1 μg) into the gastrocnemius muscle did not affect mechanical nociceptive threshold in naïve rats, exposure to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Patients who received 30 μg TTX twice daily for 4 consecutive days resulted in an analgesic response of 56.7 days, while the placebo only enabled 9.9 days [ 18 ]. There was still a significant anti-hyperalgesia effect at 24 h with topical injection of 0.03–1.0 μg /kg TTX [ 10 ]. TTX as an effective treatment at low doses has shown that 1.0–3.0 μg/kg TTX reduces the expression of mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who received 30 μg TTX twice daily for 4 consecutive days resulted in an analgesic response of 56.7 days, while the placebo only enabled 9.9 days [ 18 ]. There was still a significant anti-hyperalgesia effect at 24 h with topical injection of 0.03–1.0 μg /kg TTX [ 10 ]. TTX as an effective treatment at low doses has shown that 1.0–3.0 μg/kg TTX reduces the expression of mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no gross motor or behavioral side effects were reported after intramuscular (i.m.) administration of 1 μg TTX [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pufferfish extracts were used for centuries to alleviate neuralgia in patients affected by leprosy, reduce tetanus-related muscle spasms, and relieve pain resulting from rheumatoid arthritis [31,32]. Today, modern pharmacological studies have supported the beneficial effects of TTX on pain [15,17,[33][34][35][36]. Despite the current need for effective, non-addictive analgesics, concern around toxicity and potential for cardiac arrythmias have limited wider clinical acceptance of TTX.…”
Section: Discussionmentioning
confidence: 99%
“…If successful, TTX will be one of a select few peripherally acting analgesics. To date, preclinical studies have shown TTX to be effective at inhibiting neuropathic [13,14] and inflammatory pain [15][16][17]. In patients with moderate to severe pain due to either cancer or chemotherapy-induced neuropathy who failed other treatments, TTX was seen to reduce pain by 30% below baseline levels in some patients [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies with TTX analogue have revealed a new metabolite 4,9 anhydro‐TTX with great selectivity for Na V 1.6 (Rosker et al ., ). Furthermore, TTX has shown in vivo efficacy in preclinical pain models of inflammatory and neuropathic pain (Beloeil et al ., ; Marcil et al ., ; Alvarez and Levine, ; Salas et al ., ) (Table ). These results suggest TTX is a potential lead for further development of Na V ‐specific blockers.…”
Section: Natural Toxins Targeting Nav Channels and Applications In Pamentioning
confidence: 99%